Facial macro expression analysis - Lim, Jie Xian (Nanyang Technological University, 2024)
Facial Expression Recognition (FER) stands at the forefront of advancing human-computer interaction, enabling machines to interpret human emotions from facial expressions with unprecedented accuracy. This project embarks on the exploration and enhancement of Facial Macro Expression Analysis using cutting-edge machine learning techniques. The core objective is to develop a robust FER system capable of identifying and analyzing a wide range of human emotions with high precision, thereby contributing to the fields of psychology, surveillance, and interactive technology.